Synergistic Power: Multi-Herb Formulations and Nanotechnology in Modern Dental Care - Ragu, Kavitha; Jalihal, Sagar; Ankola, Anil V.; Sankeshwari, Roopali M.; Shankkari, Siva; Kandasamy Parimala, Yuvarani (Indian Journal of Integrative Medicine, 2025)
Herbal medicine has traditionally found its way in varying degrees into the field of oral healthcare, with many plant extracts demonstrating antimicrobial, anti-inflammatory, and antioxidant properties. With advances in dental research, the therapeutic emphasis has slowly been shifting toward multi-herb formulations rather than single-herb applications, so as to harness the synergistic effects of different phytochemicals and thereby improve therapeutic efficacy. At the same time, the advent of herbal nanotechnology has led to the improvement in the bioavailability, stability, and target delivery of difficult herbal compounds. This review focuses on the changing landscape of multi-herb and nano-herbal formulations in dental care, along with their working mechanisms, clinical applications, and potential advantages over conventional treatment. A comprehensive literature search was undertaken to identify all available data on multi-herb and nano-herbal dental products, concentrating on their antimicrobial, anti-inflammatory, and remineralizing benefits. Discussion of some important medicinal plants widely used in dentistry, viz. neem, turmeric, clove, and aloe vera, is provided along with their properties and specific applications in dentistry. The review also considers how novel delivery systems like nanoparticles and nanoemulsions can significantly enhance the therapeutic efficacy of the herbal actives. Though very promising evidence is obtained from the preliminary studies, further studies are needed to put these formulations on a firm basis.